THE INFLUENCE OF BUSINESS MODELS, BUSINESS STRATEGIES, ORGANIZATIONAL CULTURE, AND INFORMATION DIGITALIZATION ON THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS - Vicky Dzaky Cahaya Putra; Wiwi Hartika (SEAN Institute, 2023)
Uncertain economic recovery requires MSMEs to always be adaptive in order to survive carrying out operational activities in difficult times, some experts even predict a recession will occur in 2024. Having a quality Accounting Information System can encourage business entities to improve quality and maximize high public consumption. to always make improvements to inventory and sales costs. This research aims to partially examine the influence of business models, business strategies, organizational culture, and information digitalization on the quality of Accounting Information Systems. The research was carried out in order to answer the relationship between related variables which have an impact on the problems that have occurred recently. The results of the research show that the quality of the accounting information system in several MSMEs in Cimahi City can be said to be good, although in terms of recording and reporting it still needs to be improved so that the financial reports produced can be said to be of good quality in accordance with the established SAK EMKM rules. This can be seen from the test results which show through calculations The calculated t value is in the H0 rejection area, that is, the calculated t is greater than the positive value of t table so that there is a significant influence from several test results of the variables studied.